Comparative study on operation and management of public and private quarries / Shahrizal Aman Nejis - Aman Nejis, Shahrizal (2006)
Quarrying activities have been around for more than a decade in this country. Quarries normally commence operations in isolated sites and thus exist very much earlier in remote sites compared to other development projects. The quarrying industries is one of the major contributes to infrastructure development and also to the industrial minerals and dimension stone industries. Overall, the objective of this dissertation is to make a comparative study on maintenance management and operation of a public and private quarries. For the purposes of this study, the public quarry that had been chosen is JKR Quarry Pekan Awah.Temerloh Pahang and for the private quarry, LCS Quarry located at Lanchang, Pahang was chosen.